Heteroglossia and Fragmentariness in the Absent Therapist by Will Eaves - Drąg, Wojciech (Studia Anglica Posnaniensia, 2017)
In “Discourse in the Novel” Mikhail Bakhtin argues that heteroglossia - a diversity of voices or languages - is one of the essential properties of the novel. The distinct languages spoken by individual characters (referred to as “character speech”), he maintains, inevitably affect “authorial speech”. In experimental fiction, where “authorial speech” is often eliminated altogether, one can speak of the most radical instance of novelistic polyphony. Whereas in The Sound and the Fury, The Waves and B.S. Johnson’s House Mother Normal in place of the narrator the reader is presented with several parallel voices which offer an alternative version of some of the same incidents, Will Eaves’s The Absent Therapist (2014) comprises 150 one- or two-page monologues, each of which is delivered by a different nameless speaker. The book, described by reviewers as an “experimental novella”, a “miniature novel”, and an “anti-novel”, is devoid of any frame that would account for the coexistence of so many stories. The only interpretive clues are provided in the paratext: the title and the dedication from 1 Corinthians (“There are, it may be, so many kinds of voices in the world, and none of them is without signification”). They appear to invite the reading of the entire text as an amalgam of disparate (but also, in large part, desperate) voices united by their addressee - the figure of the therapist who is not there. The aim of the article is to examine Eaves’s assemblage of voices and outline the tenuous relationship between the sections. The analysis of common themes and motifs that provide a degree of qualified unity to the book’s multiple monologues is situated in the context of fragmentary writing (as practised, among others, by Burroughs and Barthes) and its postmodernist aesthetics of the collage.